Deficits in metacognitive monitoring in mathematics assessments in learners with autism spectrum disorder. (May 2016) - Brosnan, Mark; Johnson, Hilary; Grawemeyer, Beate; Chapman, Emma; Antoniadou, Konstantina; Hollinworth, Melissa
Children and adults with autism spectrum disorder have been found to have deficits in metacognition that could impact upon their learning. This study explored metacognitive monitoring in 28 (23 males and 5 females) participants with autism spectrum disorder and 56 (16 males and 40 females) typically developing controls who were being educated at the same level. Participants were asked a series of mathematics questions. Based upon previous research, after each question they were asked two metacognitive questions: (1) whether they thought they had got the answer correct or not (or 'don't know') and (2) whether they meant to get the answer correct or not (or 'don't know'). Participants with autism spectrum disorder were significantly more likely than the typically developing group to erroneously think that they had got an incorrect answer correct. Having made an error, those with autism spectrum disorder were also significantly more likely to report that they had meant to make the error. Different patterns in the types of errors made were also identified between the two groups. Deficits in metacognition were identified for the autism spectrum disorder group in the learning of mathematics. This is consistent with metacognitive research from different contexts and the implications for supporting learning in autism spectrum disorder are discussed.